EFFECTS OF FRACTURE LINEAMENTS AND IN-SITU ROCK STRESSES ON GROUNDWATER FLOW IN HARD ROCKS: A CASE STUDY FROM SUNNFJORD, WESTERN NORWAY - Henriksen H.; Braathen A. (My University, 2006)
Systematic field mapping of fracture lineaments observed on aerial photographs shows that almost all of these structures are positively correlated with zones of high macroscopic and mesoscopic fracture frequencies compared with the surroundings. The lineaments are subdivided into zones with different characteristics: (1) a central zone with fault rocks, high fracture frequency and connectivity but commonly with mineral sealed fractures, and (2) a damage zone divided into a proximal zone with a high fracture frequency of lineament parallel, non-mineralized and interconnected fractures, grading into a distal zone with lower fracture frequencies and which is transitional to the surrounding areas with general background fracturing. To examine the possible relations between lineament architecture and in-situ rock stress on groundwater flow, the geological fieldwork was followed up by in-situ stress measurements and test boreholes at selected sites. Geophysical well logging added valuable information about fracture distribution and fracture flow at depths. Based on the studies of in-situ stresses as well as the lineaments and associated fracture systems presented above, two working hypotheses for groundwater flow were formulated: (i) In areas with a general background fracturing and in the distal zone of lineaments, groundwater flow will mainly occur along fractures parallel with the largest in-situ rock stress, unless fractures are critically loaded or reactivated as shear fractures at angles around 30° to σH; (ii) In the influence area of lineaments, the largest potential for groundwater abstraction is in the proximal zone, where there is a high fracture frequency and connectivity with negligible fracture fillings. The testing of the two hypotheses does not give a clear and unequivocal answer in support of the two assumptions about groundwater flow in the study area. But most of the observed data are in agreement with the predictions from the models, and can be explained by the action of the present stress field on pre-existing fractures.
Keywords: FRACTURED ROCKS; GEOPHYSICAL METHODS; GROUNDWATER FLOW; TECTONICS; CONCEPTUAL MODELS